Effect of Self-Myofascial Release of the Lower Back on Myofascial Gliding, Lumbar Flexibility, and Abdominal Trunk Muscle Strength: A Crossover Study - Yuki Nakai; Katsutoshi Oe; Ryuko Matsuno; Ryoji Kiyama; Masayuki Kawada; Yasufumi Takeshita; Takasuke Miyazaki; Sota Araki (MDPI AG, 2023)
Roller massage has been recognized as an effective intervention for managing various conditions. However, data on the effects of roller massage on the dynamic mechanisms of the myofascial and soft tissues of the lower back are limited. This study aimed to examine the effect of the self-myofascial release of the lower back on myofascial gliding, lumbar flexibility, and abdominal trunk muscle strength using a roller massager. This crossover study included 24 college athletes who underwent three interventions-roller massage, static stretching, and control (rest). Before and after the intervention, lumbar and fascial gliding were evaluated using ultrasonography. Long-seat anteflexion (lumbar flexibility) and abdominal trunk muscle strength were assessed. The movement velocities of the subcutaneous tissue and the multifidus muscle over time were calculated using echo video analysis software, and gliding was estimated using the cross-correlation coefficient between the velocities. Gliding, lumbar flexibility, and abdominal trunk muscle strength showed significant intervention-by-time interactions. Roller massage significantly improved gliding, lumbar flexibility, and abdominal trunk muscle strength. The self-myofascial release of the lower back using a roller massager improved the lumbar/fascia gliding, lumbar flexibility, and abdominal trunk muscle strength compared to static stretching.